Analysis and optimal sizing of pneumatic drive systems for handling tasks - Raisch, Adrian; Sawodny, Oliver (Mechatronics (Oxford), 2019)
Energy savings and efficiency are declared aims of today’s politics. A large proportion of energy usage is related to manufacturing with its drive systems technologies. Especially pneumatic drive systems have a large savings potential – mostly often based on the fact that their compressed air consumption is a consequence of design, which in practice is usually done by system designers based on their experience. In this paper, we give a detailed system analysis, yielding promising optimization parameters. For the design optimization we then compare gradient-based strategies with a genetic algorithm, showing that the much more efficient gradient-based schemes are suitable for the application to pneumatic drives. Besides the usage of a standard interior-point optimization scheme, a discrete-value optimization approach is derived. The optimization results are applied to a three-drive setup, tested and validated with measurements – emphasizing the importance of optimization of pneumatic drives and the effectiveness of the discrete-value optimization.